731 RISK OF ESOPHAGEAL AND GASTRIC ADENOCARCINOMA IN MEN RECEIVING ANDROGEN DEPRIVATION THERAPY FOR PROSTATE CANCER. (17th September 2021) - Shore, Richard; Yu, Jingru; Ye, Weimin; Lagergren, Jesper; Rutegård, Martin; Akre, Olof; Stattin, Pär; Lindblad, Mats
Abstract: : There is an unexplained male predominance in the incidence of esophageal (EAC) and non-cardia gastric adenocarcinoma (GAC) which cannot be explained by known risk factors. Differences in the exposures to sex hormones may play a part in the observed sex difference. This study aimed to test the hypothesis that androgens increase the risk of EAC, cardia GAC, and non-cardia GAC. We analysed a matched cohort based on a national Swedish database of prostate cancer patients. Methods: Prostate cancer patients receiving androgen deprivation therapy (ADT) were the exposed group. Prostate cancer-free men from the general population were randomly selected and matched to the index case by birth year and county of residence, forming the unexposed control group. The participants were followed until a diagnosis of esophageal or gastric cancer, death, emigration, or end of the study period. The risk of esophageal adenocarcinoma, cardia gastric adenocarcinoma, non-cardia gastric adenocarcinoma, and esophageal squamous-cell carcinoma among ADT-exposed compared to unexposed was calculated by multivariable Cox proportional hazard regression. The hazard ratios and 95% confidence intervals were adjusted for confounders. Results: There was a risk reduction of non-cardia gastric adenocarcinoma among ADT-users compared to non-users (HR 0.49 [95% CI 0.24–0.98]). No such decreased risk was found for esophageal adenocarcinoma (HR 1.17 [95% CI 0.60–2.32]), cardia gastric adenocarcinoma (HR 0.99 [95% CI 0.40–2.46]), or esophageal squamous cell carcinoma (HR 0.99 [95% CI 0.31–3.13]). Conclusion: This study indicates that androgen deprivation therapy decreases the risk of non-cardia gastric adenocarcinoma, while no decreased risk was found for esophageal adenocarcinoma, cardia gastric adenocarcinoma, or esophageal squamous-cell carcinoma.